2022
DOI: 10.1007/s10722-022-01515-2
|View full text |Cite
|
Sign up to set email alerts
|

A multi-reference parent nested-association mapping population to dissect the genetics of quantitative traits in durum wheat

Abstract: Durum wheat (Triticum turgidum L.) breeding programs face many challenges surrounding the development of stable varieties with high quality and yield. Therefore, researchers and breeders are focused on deciphering the genetic architecture of biotic and abiotic traits with the aim of pyramiding desirable traits. These efforts require access to diverse genetic resources, including wild relatives, germplasm collections, and mapping populations. Advances in accelerated generation technologies have enabled the rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Previously, a durum NAM population was developed by crossing eight ICARDA ‘founder’ lines with two Australian durum ‘reference’ varieties Jandaroi and DBA Aurora (Alahmad et al, 2022). For this study, 11 genotypes including the reference parent DBA Aurora and 10 NAM lines, based on the SRA screenings by Alahmad et al (2019), were selected for divergent SRAs (wide and narrow) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a durum NAM population was developed by crossing eight ICARDA ‘founder’ lines with two Australian durum ‘reference’ varieties Jandaroi and DBA Aurora (Alahmad et al, 2022). For this study, 11 genotypes including the reference parent DBA Aurora and 10 NAM lines, based on the SRA screenings by Alahmad et al (2019), were selected for divergent SRAs (wide and narrow) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The two durum wheat lines, QAF0512 (Narrow) and QAF0411 (Wide) were selected from a set of F 6 generation durum lines from a nested association mapping population that were previously characterised by Alahmad et al (2019), in which they were observed to express contrasting seminal root angles (QAF0512 = 41° and QAF0411 = 82). These lines have also been included in a series of further screenings and targeted studies that confirmed their contrasting seminal root angles and relationship with RSA, whilst also displaying similarities in root system biomass, tiller number, growth rate, and time to flowering (Alahmad et al 2022;van der Bom et al 2023). The two sorghum lines, B35 (narrow) and SC999-14E (wide) were selected from a previously characterised set of inbred lines (Mace et al 2012) in which they were observed to express contrasting nodal root angles (B35 = 28° and SC999 = 46° for the first flush of nodal roots, relative to a vertical plane).…”
Section: Plant Materialsmentioning
confidence: 99%
“…genotypes (wide and narrow root angle) to combinations of starter-P and deep P bands. Previous studies on these crops have focused on genetic variability and control (Alahmad et al 2019(Alahmad et al , 2022Mace et al 2012;Singh et al 2010Singh et al , 2011Singh et al , 2012. Building on these, the aim of the current study was to understand how contrasting genotypes respond to complex target environments.…”
Section: Introductionmentioning
confidence: 99%
“…Moving forward, pinpointing specific genetic markers linked to these traits could revolutionize oat breeding programs. Furthermore, diverse parents can be used to develop mapping population and investigate the genetics of yield and quality traits [ 13 ]. Given the understanding above and recognizing a research gap regarding the absence of an appropriate variety of oat grains that comprehensively addresses both nutritional and animal health aspects, this study aims to analyze different types of oats to understand how they vary genetically in terms of how much they produce, their physical characteristics, and what nutrients they contain.…”
Section: Introductionmentioning
confidence: 99%